2006
DOI: 10.1063/1.2200591
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale n-channel and ambipolar organic field-effect transistors

Abstract: Articles you may be interested inElectrical characteristics of single-component ambipolar organic field-effect transistors and effects of air exposure on them

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 18 publications
(19 reference statements)
0
24
0
1
Order By: Relevance
“…[217] Studies of pentacene films by conducting-probe AFM showed that both electrons and holes could be injected into pentacene monolayer islands, and that both carrier types delocalized throughout the island. [218] Early approaches to ambipolar transistors have used 22 as the p-type material in bilayer devices-these are typically fabricated using either a fullerene [219] or perylene diimide [220] as the n-type material. However, in these cases 22 is exploited for its high hole, rather than eletron, mobility.…”
Section: Stabilitymentioning
confidence: 99%
“…[217] Studies of pentacene films by conducting-probe AFM showed that both electrons and holes could be injected into pentacene monolayer islands, and that both carrier types delocalized throughout the island. [218] Early approaches to ambipolar transistors have used 22 as the p-type material in bilayer devices-these are typically fabricated using either a fullerene [219] or perylene diimide [220] as the n-type material. However, in these cases 22 is exploited for its high hole, rather than eletron, mobility.…”
Section: Stabilitymentioning
confidence: 99%
“…[217] Kraftmikroskopische Untersuchungen ergaben, dass sowohl Elektronen als auch Löcher in Inseln in Pentacenmonoschichten injiziert werden können und beide Ladungsträgertypen über die Inseln delokalisiert sind. [218] Um ambipolare Transistoren zu erhalten, wurde 22 schon früher als p-Halbleiter in Doppelschichttransistoren eingesetzt, die zumeist Fullerene [219] oder Perylendiimid [220] als n-Halbleiter enthielten. Entscheidend war hierbei die hohe Beweglichkeit der Löcher (und nicht der Elektronen) in 22.…”
Section: Stabilitätunclassified
“…We investigated the recently introduced PDI-8CN 2 [5][6][7][8][9][10][11] with the chemical structure shown in Fig. 1.…”
mentioning
confidence: 99%